Financial and regulatory assessment of Mobile Network Sharing as a trigger of cost efficient 5G rollout in CEE - Gábor Földes (International Telecommunications Society (ITS), 2022)
Telecommunication sector faces to parallel investments into both fiber and 5G, however due to monetization challenges, return on investments often lag behind normal profit expectations. Co-investment, like mobile network sharing can promote cost efficiency, however cooperation raises regulatory concerns related to competition and innovation in the EU. The purpose of this paper to assess the Czech and Hungarian mobile network sharing agreements in CEE that both show higher degree of cooperation, therefore not cleared by the competition regulations, however has been placed in unchanged form for 8 years. The research question is to assess the procompetitive and anticompetitive theoretical aspects and actual impacts of opposed cooperation in terms of net effect, whether benefits outweigh potential drawbacks in particular to foreseen 5G rollout. The research methodology covers the empirical comparison of Czech and Hungarian market data related to market shares, prices and data traffic volume, as well as network quality data on coverage and capacity in 2014-2021-time frame. The main finding is that, although live network sharing agreements have been opposed, main anticompetitive effects could not be justified, and majority of procompetitive benefits fails to be rejected, with the exemption of efficiency gains pass through customers that remains unclear. Despite of benefits may outweigh potential drawbacks even in these not recommended cases, due to lack of regulatory clearance, the 5G rollout launched without sharing, causing social welfare loss. The originality of the paper that it provides an empirical research on such a live network sharing case that is not recommended and not cleared, as sharing contains active network elements and even spectrum, highlighting that even these cases' procompetitive advantages may outweigh anticompetitive ones.
Keywords: 330; 5G; mobile network sharing; cost efficiency; coopetition; competition regulation